A new proximate structure for the APB (111) in L12 compounds. (June 2020) - Vamsi, K.V.; Pollock, Tresa M.
Abstract: A new approach which involves a diffuse multi-layer fault model coupled with a cluster approach to statistical mechanics (CASM) infrastructure has been developed to identify the proximate structure for the antiphase boundary (APB) on 111 planes in L12 . We report a new structure, ' γ a ′ ' which approximates the bonding environment of an APB better than a previously reported structure, 'ω'. Density functional theory calculations were employed to predict the APB energies from structural energies of γ a ′ and L12 and were validated against estimations from supercell methods for several binary compounds. The implications of the discovery of the γ a ′ are discussed. Graphical abstract: Image, graphical abstract